Classification of cesarean section through Robson criteria: an emerging concept to audit the increasing cesarean section rate - Kant, Anita; Mendiratta, Shweta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: There has been an increase in rate of cesarean section over last five decades. This is a matter of international public health concern as it increases the cesarean section related maternal morbidity. The aim of the present study was to audit the increasing rate of caesarean section. Methods: In the present study, all cases delivered by cesarean section during the period of six months were recorded and classified according to Robson's 10 group classification system. This was an attempt to see which clinically relevant groups contributed most to the cesarean deliveries. Results: There was a trend of increased percentage of cesarean section in group 5 and 2 respectively in present study. Increasingly sedentary lifestyle and poor tolerance to pain are adding to cesarean delivery on maternal request. Conclusions: We should judiciously make use of vaginal birth after cesarean section but not at the cost of maternal or fetal health. Standardization of indication of cesarean deliveries, regular audits and definite protocols in hospital will aid in curbing the rate of cesarean deliveries in hospitals.